Critical Care Recovery Center: a model of agile implementation in intensive care unit (ICU) survivors. (30th December 2020) - Wang, Sophia; Hanneman, Philip; Xu, Chenjia; Gao, Sujuan; Allen, Duane; Golovyan, Dmitry; Kheir, You Na; Fowler, Nicole; Austrom, Mary; Khan, Sikandar; Boustani, Malaz; Khan, Babar
ABSTRACT: Background: As many as 70% of intensive care unit (ICU) survivors suffer from long-term physical, cognitive, and psychological impairments known as post-intensive care syndrome (PICS). We describe how the first ICU survivor clinic in the United States, the Critical Care Recovery Center (CCRC), was designed to address PICS using the principles of Agile Implementation (AI). Methods: The CCRC was designed using an eight-step process known as the AI Science Playbook. Patients who required mechanical ventilation or were delirious ≥48 hours during their ICU stay were enrolled in the CCRC. One hundred twenty subjects who completed baseline HABC-M CG assessments and had demographics collected were included in the analysis to identify baseline characteristics that correlated with higher HABC-M CG scores. A subset of patients and caregivers also participated in focus group interviews to describe their perceptions of PICS. Results: Quantitative analyses showed that the cognitive impairment was a major concern of caregivers. Focus group data also confirmed that caregivers of ICU survivors ( n = 8) were more likely to perceive cognitive and mental health symptoms than ICU survivors ( n = 10). Caregivers also described a need for ongoing psychoeducation about PICS, particularly cognitive and mental health symptoms, and for ongoing support from other caregivers with similar experiences. Conclusions: Our study demonstrated how the AI Science Playbook was used to build the first ICU survivor clinic in the United States. Caregivers of ICU survivors continue to struggle with PICS, particularly cognitive impairment, months to years after discharge. Future studies will need to examine whether the CCRC model of care can be adapted to other complex patient populations seen by health-care professionals.